Implementasi Artificial Intelligence untuk Penguatan Manajemen Pembelajaran Akidah Akhlak di Era Digital: Studi Kasus Pondok Pesantren Raudhatul Mujawwidin Tebo - Lailil Karmi; Mabruri Mabruri; Ulfa Adilla; Baili Baili; Nur Aysah; Nurhasanah Nurhasanah (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
This study analyses the implementation of Artificial Intelligence (AI) for strengthening the management of Akidah Akhlak learning in the digital era at Pondok Pesantren Raudhatul Mujawwidin, Tebo. The rapid development of digital technology requires Islamic educational institutions to adapt to technological innovation in order to enhance the effectiveness of the learning process. A qualitative approach with a case study design was employed. Data were collected through participant observation, in-depth interviews and documentation, involving the head of the pesantren and Akidah Akhlak teachers as primary informants. Data were analysed through the interactive model of data reduction, data display and verification, while the trustworthiness of the findings was tested through source and method triangulation. The results indicate that AI supports the entire cycle of Akidah Akhlak learning management, from planning, implementation, evaluation, to monitoring. AI is utilised for generating digital teaching materials, analysing students learning needs, presenting moral case study scenarios relevant to modern life, and accelerating assessment. However, several challenges remain, including limited teacher digital literacy, inadequate technological infrastructure, and the need for ethical guidelines aligned with Islamic values. Continuous teacher training and internal pesantren policies are therefore essential for optimising AI use. This study contributes a contextual framework that positions AI as a pedagogical assistant rather than a replacement for the kiai santri relationship, in order to ensure that the integration of AI strengthens adaptive, effective and value-based Akidah Akhlak learning.